Performance, captação e foco das famílias de fundos de investimento - Robert Aldo Iquiapaza Coaguila (2009)
The mutual funds are institutional investors that promote the development of capital markets, improving the liquidity and transparency, providing advantages of portfolio diversification, especially to retail investors. At the same time, there is a tendency to build big complexes orfund families. In this study we analyzed the impact of fund family focus in generating value for shareholders of investment funds in Brazil. Specifically, the study aimed to determine if there is a global specialization gain, and to measure if there is an effect of familiesspecialization on fund flow, on performance, and on performance persistence of the individual funds. The period was from 2003 to June 2009. The objectives were developed in two parts. For the first objective, we used indicators to measure the degree of focus among the investment objectives and to classify the fund families into specialized and not specialized; in the analysis were used parametric and nonparametric techniques; and it was determined that in the period of study there was no specialization gain. On average, not specialized families had better indicators but not statistically significant; however, the variability in performance indicators was statistically higher for specialized families. In the second part of the study it was examined the effect of fund families specialization on net fund flows, fund performanceand fund performance persistence. We used multiple and logistic regression techniques for panel data and also nonparametric tests; after controlling for other variables, in 2008 specialization had weak effect, with negative sign, on net fund flows. There was an inverse effect of specialized families on the expected return only in active stock funds and active multimarket funds. It was also determined that in the multimarket funds focused families have a lower percentage of persistent winners funds and a higher percentage of persistent losers funds, but among fixed income funds these families had more persistent winners funds.Finally, answering the research question, in aggregate level, it was not identified a specialization gain when analyzing the performance of family funds for their funds investors. In the analysis of individual funds, among multimarket funds the focused families had the worst combination of funds with performance persistence. As not focused families are usuallylarger in assets and in number of funds, it appears that the effects of economies of scale are still superior to the specialization gain.